Context-dependent effects on the hydrophilicity/hydrophobicity of side-chains during reversed-phase high-performance liquid chromatography: Implications for prediction of peptide retention behaviour - Mant, C.T. (2006)
The present study set out to investigate whether observed relative hydrophilicity/hydrophobicity values of positively charged side-chains (with Lys and Arg as representative side-chains) or hydrophobic side-chains (with Ile as the representative side-chain) were context-dependent, i.e., did such measured values vary depending on characteristics of the peptides within which such side-chains are substituted (overall peptide hydrophobicity, number of positive charges) and/or properties of the mobile phase (anionic counterions of varying hydrophobicity and concentration)? Reversed-phase high-performance liquid chromatography (RP-HPLC) was applied to two series of four synthetic peptide analogues (+1, +2, +3 and +4 net charge), the only difference between the two peptide series being the substitution of one hydrophobic Ile residue for a Gly residue, in the presence of anionic ion-pairing reagents of varying hydrophobicity (HCOOH ≈ H(3)PO(4) < TFA < PFPA < HFBA) and concentration (2–50 mM). RP-HPLC of these peptide series revealed that the relative hydrophilicity of Lys and Arg side-chains in the peptides increased with peptide hydrophobicity. In addition the relative hydrophobicity of Ile decreased dramatically with an increase in the number of positive charges in the peptide, this hydrophobicity decrease being of greater magnitude as the hydrophobicity of the anionic ion-pairing reagent increased. These results have significant implications in the prediction of peptide retention times for proteomic applications.